Model test for the tensioning construction process of a large-span prestressed suspended dome. Issue 4 (April 2017) - Liu, Xuechun; Zhang, Yiwen; Zhang, Ailin; Wu, Liang
Before being tensioned, the stiffness of the upper reticulated shell of a prestressed suspended dome is small, and the lower cable–strut system is completely flexible. The shape and stiffness of the structure constantly change during the construction process; therefore, a construction experiment needed to be performed to ensure the success and safety of the tensioning process for practical engineering. A tensioning experiment was performed on a reduced scale model of a large-span suspended dome. The safety, internal forces, joint displacements, and cable tensions during the tensioning process were studied. The effects of the sequence, times, and magnitudes of the loop cable tensioning were studied. The unfavorable factors of friction loss at the cable–strut joint, tensioning sequence loss, and out-of-sync tensioning on the tensioning points were evaluated, and measures to reduce the friction loss were then proposed. Two tensioning schemes were tested, compared, and used to predict the potential difficulties in practical engineering construction. An optimized tensioning scheme was developed for practical engineering.